2013
DOI: 10.1002/ajpa.22438
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress increases variability in the expression of dental cusps

Abstract: Teeth are an important model for developmental studies but, despite an extensive literature on the genetics of dental development, little is known about the environmental influences on dental morphology. Here we test whether and to what extent the environment plays a role in producing morphological variation in human teeth. We selected a sample of modern human skulls and used dental enamel hypoplasia as an environmental stress marker to identify two groups with different stress levels, referred to as SG ("stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 83 publications
5
29
0
3
Order By: Relevance
“…The fact that dental traits are equally or more homoplastic than cranial and postcranial characters in primates and other mammals, and that trees based on dental and skeletal characters are not always consistent with those derived from molecular data has been documented extensively (Kay, 1990;Harris & Disotell, 1998;Ross et al 1998;S anchez-Villagra & Williams, 1998). A recent study by Riga et al (2014) in recent humans also found that environmental stress significantly increases the morphological variability and number of cusps within a tooth. Therefore, we highlight the need of using different lines of evidence for character definition and selection, which ultimately will lead to more reliable phylogenetic reconstructions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The fact that dental traits are equally or more homoplastic than cranial and postcranial characters in primates and other mammals, and that trees based on dental and skeletal characters are not always consistent with those derived from molecular data has been documented extensively (Kay, 1990;Harris & Disotell, 1998;Ross et al 1998;S anchez-Villagra & Williams, 1998). A recent study by Riga et al (2014) in recent humans also found that environmental stress significantly increases the morphological variability and number of cusps within a tooth. Therefore, we highlight the need of using different lines of evidence for character definition and selection, which ultimately will lead to more reliable phylogenetic reconstructions.…”
Section: Discussionmentioning
confidence: 85%
“…A recent study by Riga et al. () in recent humans also found that environmental stress significantly increases the morphological variability and number of cusps within a tooth. Therefore, we highlight the need of using different lines of evidence for character definition and selection, which ultimately will lead to more reliable phylogenetic reconstructions.…”
Section: Discussionmentioning
confidence: 86%
“…Although permanent molars were not included in their study, results presented here are consistent with their findings. Similarly, Riga, Belcastro, and Moggi‐Checci () documented increased, directional variation in molar cusp number and size in a stressed (vs. nonstressed) sample, indicating that environment can act “nonrandomly” on developmental parameters throughout crown formation. Our results suggest caution is needed in selecting which side to use in dental biodistance analyses.…”
Section: Discussionmentioning
confidence: 93%
“…Modularity is also evident in the dissociations that can occur between dental development, somatic growth, and aspects of life history. Phenotypic plasticity in the dentition is reflected in environmental effects on variation in tooth size (Garn et al, ), dental morphology (Riga et al, ), and dental eruption ages (Garn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Garn, Osborne, and McCabe (), however, also showed that prenatal factors could have strong effects on tooth size, establishing that environment can be an important factor. Years later, Riga, Belcastro, and Moggi‐Cecchi () linked developmental stress to variation in crown traits, demonstrating environmental effects on tooth morphology as well.…”
Section: Modern/recent Human Dental Variationmentioning
confidence: 99%